We first factor out an x and then we divide every term by x.
So, mx divided by x = m.
Then 7nx divided by x = 7n.
We now divide both sides of the equation by (m + 7n).
Final answer: x = 7/(m + 7n).
By the way, you can also write the final answer as x = 7/(7n + m).
Just in case you are looking to solve for n, this is how it is done.
Subtract mx from both sides.
7nx = 7 - mx
Now divide both sides by 7x.
n = (7 - mx)/7x
Remember, the first reply is correct but I just wanted to show you what to do should you need to solve for n in this example.